SMG101 : Understanding sport organization / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2023)
This course is designed to provide the student with fundamental knowledge necessary to manage individuals, groups and processes in the sport setting as well as issues facing sport organizations and how management techniques can be applied to solve management problems. In addition, the student will gain an appreciation for segments of the sports industry and potential career opportunities available in the fields.